2015
DOI: 10.1007/s10549-015-3592-z
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic profiling of inflammatory breast cancer cases reveals a high frequency of clinically relevant genomic alterations

Abstract: Inflammatory breast cancer (IBC) is a distinct clinicopathologic entity that carries a worse prognosis relative to non-IBC breast cancer even when matched for standard biomarkers (ER/PR/HER2). The objective of this study was to identify opportunities for benefit from targeted therapy, which are not currently identifiable in the standard workup for advanced breast cancer. Comprehensive genomic profiling on 53 IBC formalin-fixed paraffin-embedded specimens (mean, 800× + coverage) using the hybrid capture-based F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 57 publications
3
62
1
Order By: Relevance
“…Ross et al reported a comprehensive genomic profiling on 53 IBC, formalin-fixed, paraffin-embedded specimens using the hybrid capture-based, FoundationOne™ assay [39]. The 53 sequenced IBC cases harbored a total of 266 genomic alterations (GA) with an average of 5.0 GA/tumor (range 1–15).…”
Section: Genomic Aberrations In Ibc Vs Non-ibcmentioning
confidence: 99%
See 2 more Smart Citations
“…Ross et al reported a comprehensive genomic profiling on 53 IBC, formalin-fixed, paraffin-embedded specimens using the hybrid capture-based, FoundationOne™ assay [39]. The 53 sequenced IBC cases harbored a total of 266 genomic alterations (GA) with an average of 5.0 GA/tumor (range 1–15).…”
Section: Genomic Aberrations In Ibc Vs Non-ibcmentioning
confidence: 99%
“…In the TNBC subset of IBC, 8/19 (42%) showed MYC amplification (median copy number 8X, range 7–20) as compared to 9/32 (28%) in non-TNBC IBC (median copy number 7X, range 6–21). Although at 32%, the MYC amplification in IBC appeared to represent enrichment in this tumor type, comparison with the 24% MYC amplification rate in the non-IBC breast cancers did not reach statistical significance ( p = 0.26) [39]. While these small studies offer some insights in novel molecular differences, larger studies are needed to confirm and validate differences.…”
Section: Genomic Aberrations In Ibc Vs Non-ibcmentioning
confidence: 99%
See 1 more Smart Citation
“…A greater frequency of HER2 and EGFR overexpression among IBC cases has been reported, occurring in 50% and 30% of patients, respectively [8]. Genomic profiling techniques have led to the identification of genes that are potentially involved in disease development [911]; however, HER2-positive IBC has not been characterised through deep exome sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…IBC is frequently HER2-overexpressing, and the disease’s hallmark is the clinical inflammatory symptoms on the breast skin due to numerous dermal lymphatic emboli. Like in other cancer types, genomic profiling has led to identification of multiple genes that are involved in IBC [4,5]. Assessments of molecular features and quantitative measures of intratumor heterogeneity are now in the translation phase from the research setting, and their clinical validity is being tested [6,7].…”
mentioning
confidence: 99%